Cross-examination of sexual assault complainants on previous sexual behaviour: views from the barristers' row - Hoyano, L (Sweet and Maxwell, 2019)
This study constitutes the largest empirical study of the use of previous sexual behaviour evidence in sexual offence trials in the courts of England and Wales ever conducted. It is impossible to understand how such evidence is handled in trials merely from reading reported judgments, because these reflect only cases which the defence has appealed to the Court of Appeal on the basis that such evidence was wrongly excluded by the trial judge, since the prosecution does not have an equivalent right to seek leave to appeal. The data collected from criminal barristers examines, in depth, 377 cases involving 565 complainants, which proceeded to trial in 105 Crown Courts centres in the 24 months immediately prior to November 2017. This study is unique in collecting data on applications to use previous sexual behaviour evidence in respect of all sexual offences, not just rape, and without any restrictions on complainants as to gender or age. Many children and adolescents feature in the sample. So too do many historical complaints, and many cases involving multiple complainants. Perhaps most importantly, it is unique in eliciting information from the 140 anonymous barristers who were directly involved in prosecuting or defending these cases in the sample, and who know best what happened, not only in the public court room but also in the closed court room and in the robing room. They in turn are highly unusual in adversarial legal systems in ‘walking both sides of the street’, possible only due to the existence of the independent Bar, available to be instructed by the Crown Prosecution Service or by the defence in any case. They therefore have a uniquely balanced view of the criminal justice system.